Finger Joint Cartilage Evaluated by Semiquantitative Ultrasound Score in Patients With Rheumatoid Arthritis. Issue 2 (1st February 2021) - Ogura, Takehisa; Hirata, Ayako; Hayashi, Norihide; Imaizumi, Chihiro; Ito, Hideki; Takenaka, Sayaka; Inoue, Yuki; Takakura, Yuto; Mizushina, Kennosuke; Katagiri, Takaharu; Kameda, Hideto
Abstract : Objective: Joint destruction in rheumatoid arthritis (RA) includes both bone and cartilage lesions. Since joint space narrowing (JSN) is not a direct evaluation of cartilage using radiography, we aimed to examine the validity of ultrasound (US) cartilage evaluation using a semiquantitative method in patients with RA. Methods: We enrolled 103 patients with RA who were in remission or showing low disease activity and 42 healthy subjects. The cartilage thickness of the bilateral metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints of the second to fifth fingers was measured by US, and the recorded images were scored semiquantitatively using a scale of 0–2. In addition, the JSN of the corresponding joints was scored using a hand radiograph. The relationships between total cartilage thickness, its semiquantitative score, and JSN score were assessed using Spearman's rank correlation coefficients. Results: Total cartilage thickness was significantly thinner in patients with RA compared to healthy subjects for both the MCP and PIP joints (both P < 0.001). The semiquantitative sum of 16 joints ranged from 2 to 26 (median 8) in patients with RA, which was significantly greater than the 0–11 (median 4) in healthy subjects ( P < 0.001). In patients with RA, the semiquantitative score showed a significant negative correlation with cartilage thickness (ρ = −0.64, P < 0.001) and a significant positive correlation with JSN score (ρ = 0.66, P < 0.001). Furthermore, these scores showed a significant correlation with RA disease duration. Conclusion: A simplified and direct evaluation of finger joint cartilage damage by semiquantitative US score is valid and useful for patients with RA.